Peripheral Intravenous Cannula Insertion and Use in the Emergency Department: An Intervention Study. (20th November 2017) - Hawkins, Tracey; Greenslade, Jaimi H.; Suna, Jessica; Williams, Julian; Rickard, Claire M.; Jensen, Matthew; Donohue, Maria; Cho, Elizabeth; Hise, Christopher Van; Egerton‐Warburton, Diana; Cullen, Louise
Abstract: Objectives: The objective was to examine cannulation practice and effectiveness of a multimodal intervention to reduce peripheral intravenous cannula (PIVC) insertion in emergency department (ED) patients. Methods: A prospective before and after study and cost analysis was conducted at a single tertiary ED in Australia. Data were collected 24 hours a day for 2 weeks pre‐ and post implementation of a multimodal intervention. PIVC placement and utilization within 24 hours were evaluated in all eligible patients. Results: A total of 4, 173 participants were included in the analysis. PIVCs were placed in 42.1% of patients' pre intervention and 32.4% post intervention, a reduction of 9.8% (95% confidence interval [CI] = 6.8 to –12.72%). PIVC usage within 24 hours of admission was 70.5% pre intervention and 83.4% post intervention, an increase of 12.9% (95% CI = 8.8% to 17.0%). Sixty‐six patients were observed in the ED for cost analysis. The mean time per PIVC insertion was 15.3 (95% CI = 12.6 to 17.9) minutes. PIVC insertion cost, including staff time and consumables per participant, was A22.79 (95% CI = A19.35 to A26.23). Conclusions: The intervention reduced PIVC placement in the ED and increased the percentage of PIVCs placed that were used. This program benefits patients and health services alike, with potential for large cost savings.